1994
DOI: 10.1021/bi00251a018
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Transfer between Small Unilamellar Vesicles and Single Bilayers on a Solid Support: Self-Assembly of Supported Bilayers with Asymmetric Lipid Distribution

Abstract: The transfer of lipids between small unilamellar vesicles of either dimyristoylphosphatidylcholine (DMPC), dimyristoylphosphatidylglycerol (DMPG), or dioctadecyl diammonium bromide (DODAB) and a single bilayer on a solid support of chain perdeuterated DMPC-d54 has been studied by time-resolved ATR infrared spectroscopy, deuterium NMR, and DSC. The IR method was used for measuring the transfer kinetics and the amount of lipid transferred to the supported bilayer, while NMR was employed for the assessment of mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
48
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 23 publications
7
48
0
1
Order By: Relevance
“…This phenomenon was somewhat unexpected in light of the fact that NH 2 groups, having a positive charge at neutral pH, would tend to repel each other due to charge repulsion rather than forming clusters. A similar experimental observation was reported before [22, 23] where it was found that charged and uncharged phospholipids segregated when blended and deposited on negatively charged silica beads. [22] In this case, it was concluded that the driving force for this phenomenon was mainly due to the electrostatic potential arising from the silica beads.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…This phenomenon was somewhat unexpected in light of the fact that NH 2 groups, having a positive charge at neutral pH, would tend to repel each other due to charge repulsion rather than forming clusters. A similar experimental observation was reported before [22, 23] where it was found that charged and uncharged phospholipids segregated when blended and deposited on negatively charged silica beads. [22] In this case, it was concluded that the driving force for this phenomenon was mainly due to the electrostatic potential arising from the silica beads.…”
supporting
confidence: 88%
“…A similar experimental observation was reported before [22, 23] where it was found that charged and uncharged phospholipids segregated when blended and deposited on negatively charged silica beads. [22] In this case, it was concluded that the driving force for this phenomenon was mainly due to the electrostatic potential arising from the silica beads. The phase segregation phenomenon has also been observed in binary self-assembly monolayers (SAM) of n-alkanethiols on Au{111} [24, 25] surfactant-coated nanoparticles and surfactant-coated flat substrates.…”
supporting
confidence: 88%
“…28 Transfer experiments of h DMPC -SUV to planar d-DMPC substrates show that the amount of lipid transferred is greatest near T m . 13 In the case of supported lipid bilayers, there can also be defects in regions where there are exposed surfaces, i.e., where the lipid has not formed a continuous lipid bilayer, as has been observed by AFM for planar SLBs. 41 Bare patches of exposed SiO 2 can result from the initial bilayer formation since the surface areas of the lipids from the SUVs and the surface area of the SiO 2 cannot be matched precisely, particularly if the surface of the SiO 2 is rough and since there is always a distribution of vesicles and NP-SiO 2 sizes.…”
Section: ■ Discussionmentioning
confidence: 90%
“…A surface may stabilize the adsorbed SUVs by increasing 0021-9797/$ -see front matter Ó 2010 Elsevier Inc. All rights reserved. doi:10.1016/j.jcis.2010.04.087 the activation energy barrier for lipid desorption from the supported membrane, while inhibition of collisions between SUVs and supported bilayers also reduces the lipid exchange rate [26]. Bayerl et al observed a difference in the phase transition temperature of vesicle bilayers in aqueous media and solid supported bilayers [27], which they concluded was due to increased demixing of two lipids in the medium in the two-phase region with increasing curvature due to lowering of the lateral pressure.…”
Section: Introductionmentioning
confidence: 99%